Peran Tingkat Penyelesaian Tindak Lanjut Rekomendasi Hasil Pemeriksaan Dalam Memoderasi Faktor Kelemahan Sistem Pengendalian Internal - Triono Triono; Subowo Subowo (Universitas Gorontalo, 2020)
This study aims to determine the role of the level of follow up TLRHP in moderating the factors that influence the weaknesses of the district / city local government’s internal control system in Central Java Province in 2014-2016. The population in this study are total of 35 districts / cities. This study uses secondary data obtained by documentation studies. The sampling technique used in this study is a saturated sample technique. This study uses descriptive statistical techniques, classic assumption tests, and moderation regression analysis with absolute difference value test models processed using IBM SPSS 23 applications. Government size, local income, capital expenditure, the level of completion of the follow-up of the audit results and moderation result together influence the weaknesses of the internal control system. The level of completion of the follow-up of the audit results has a significant negative effect on the weaknesses of the internal control system, the completion level of follow-up recommendations results in moderating the relationship of capital expenditure with the weaknesses of the internal control system